Pengaruh Keterampilan Kerja Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Bagian Produksi PT. Lungnajaya Sejahtera Prima - Hendriani; Rahwana, Kusuma Agdhi; Oktaviani, Nita Fauziah (Utami Publisher, 2024)
This study aims to determine the simultaneous and partial effects of work skills variables and work discipline variables on work productivity. The population used in this study were 86 employees of the production department of PT Lungnajaya Sejahtera Prima. The method used in this research is causality quantitative research. The sample selection used is accidental sampling technique with the slovin formula. The data sources in this study are primary data and secondary data. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the results of the study, it is concluded that simultaneously work skills and work discipline have a significant effect on work productivity. Partially work skills have no significant effect on work productivity. Work discipline partially has a significant effect on work productivity.